ANALISIS SEMANTIK PADA LAGU PENYANGKALAN OLEH FOR REVENGE: ARTIKEL KONSEPTUAL - Sinta Sianipar; Anggun Saputri; Maria Evelyntina Siregar; Sari Rahmdani; Inayah Hanum; Anggia Putri (Journal Education and Government Wiyata, 2025)
The song Penyangkalan is a For Revenge song that carries the Alternative, hardcore and rock genres. This song tells the story of someone who denies being in a toxic relationship, struggling to deal with trauma, pain and the inability to face reality. With a semantic approach, this article aims to outline how the elements in the song "Penyangkalan" convey a message and form a deep emotional resonance for the listener. Data collection for this article used Library Research. Overall, this song illustrates that denial is a psychological trap that perpetuates suffering, creating a tense atmosphere that makes listeners drift into inner turmoil.